Optimism in adults born preterm: Systematic review and individual-participant-data meta-analysis - Rachel K. Robinson (Public Library of Science (PLoS), 2021)
Aim Preterm birth(<37 gestational weeks) is associated with numerous adversities, however, data on positive developmental outcomes remain limited. We examined if preterm and term born(≥37 gestational weeks) adults differ in dispositional optimism/pessimism, a personality trait associated with health and wellbeing. We assessed if birth weight z-score, neurosensory impairments and parental education modified the outcome. Methods We systematically searched PubMed and Web of Science for cohort or case-control studies(born ≥ 1970) with data on gestational age and optimism/pessimism reported using the Life-Orientation-Test-Revised in adulthood(≥18 years). The three identified studies(Helsinki Study of Very Low Birth Weight Adults; Arvo Ylppö Longitudinal Study; Avon Longitudinal Study of Parents and Children) provided data for the two-step random-effects linear regression Individual-Participant-Data meta-analysis. Results Preterm and term borns did not differ on optimism(p = 0.76). Preterms scored higher on pessimism than term borns(Mean difference = 0.35, 95%Confidence Interval 0.36, 0.60, p = 0.007), although not after full adjustment. Preterm born participants, but not term born participants, with higher birth weight z-score, had higher optimism scores (0.30 raw score units per standard deviation increase, 95% CI 0.10, 0.49, p = 0.003); preterm vs term x birth weight z-score interaction p = 0.004). Conclusions Preterm and term born adults display similar optimism. In preterms, higher birth weight may foster developmental trajectories promoting more optimistic life orientations.